An operational process for goal-driven definition of measures. - Briand, L.C (IEEE Transactions on software engineering)
We propose an approach (GOM/MEDEA) for defining measures of product attributes in software engineering. The approach is driven by the experimental goals of measurement, expressed via the GQM paradigm, and a set of empirical hypotheses. To make the empirical hypotheses quantitatively verifiable, GQM/MEDEA supports the definition of theoretically valid measures for the attributes of interest based on their expected mathematical properties. The empirical hypotheses are subject to experimental verification. This approach integrates several research contributions from the literature into a consistent, practical, and rigorous approach.